Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Sockeye salmon - Pauley, Gilbert B.; Risher, Ron. (Washington, D.C. U.S. Department of the Interior, 1989)
U. S. Fish and Wildlife Service. Biological report ; 82(11.116)
Keywords: Sockeye salmon--Pacific Northwest